Vitamin D as an adjunct to subcutaneous allergen immunotherapy in asthmatic children sensitized to house dust mite - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (WILEY, 2014)
BackgroundWe aimed to investigate the efficacy, safety, and T regulatory cell response of vitamin D as an adjunct to allergen-specific immunotherapy (IT). MethodsFifty children with asthma and receiving pharmacotherapy were randomized into three groups as: subcutaneous IT (SCIT) along with vitamin D supplementation (650U/day; n: 17), SCIT alone (n: 15), and pharmacotherapy alone (n: 18). All patients were evaluated at baseline, 6th and 12th months for scorings of symptoms and medication, skin prick testing, total IgE, specific IgE, and Der p 1-specific IgG4. In addition, D.pteronyssinus-induced CD4(+)CD25(+)FOXP3(+)T regulatory cell percentage, intracellular Foxp3 expression, and peripheral blood mononuclear cell IL-10 and TGF- responses were assessed. ResultsIn the SCIT+vitamin D and SCIT alone groups, total asthma symptom score (TASS), total symptom score (TSS), and total medication scores (TMS) were significantly lower than pharmacotherapy group at the end of 1year. While the comparison of delta values ( 6th and 12th month-baseline) of those scores revealed no significant differences between the two IT groups, TASS at the 6th month was lower in the SCIT+vitamin D group compared with others. There was a significant and positive trend in the levels of Der p 1-specific IgG4 in both IT groups throughout the study period. Whereas the levels of Der p 1-induced IL-10 and TGF- were similar between IT groups, the mean fluorescence intensity of Foxp3 was highest in the SCIT+vitamin D group compared with others at the 12th month. The rate of discontinuation of inhaled corticosteroid (ICS) was 6/17 in SCIT+vitamin D, 3/15 in SCIT, and 0/18 in the pharmacotherapy group (P=0.02). ConclusionBoth SCIT groups fared better than pharmacotherapy alone at the end of 1year. Although the clinical and immunologic outcomes were mostly similar between the two IT groups, some favorable outcomes of vitamin D warrant further investigation in more selected populations with varying doses as adjunct to IT.
Keywords: asthma; children; immunotherapy; regulatory T cells; vitamin D; REGULATORY T-CELLS; D DEFICIENCY; EXPRESSION; INDUCTION; CYTOKINES; EFFICACY; D-3